2018
DOI: 10.1039/c8fo00353j
|View full text |Cite
|
Sign up to set email alerts
|

A positive impact on the serum lipid profile and cytokines after the consumption of a plant sterol-enriched beverage with a milk fat globule membrane: a clinical study

Abstract: The hypocholesterolemic effect and the modification of serum biomarkers of a dietary plant sterol (PS) intake, cholesterol precursors and cytokines after the consumption of milk-based fruit beverages with a milk fat globule membrane were evaluated by a randomized, double-blind, crossover, multiple dose bioavailability study. Postmenopausal women (n = 38) consumed daily 250 mL of a beverage with or without 2 g of PS added during 6 weeks in each of the study periods. With the intake of the PS-added beverage, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…In this sense, milk-based fruit beverages could be a suitable nutritional matrix for this purpose due to its low-fat content and good sources of bioactive compounds such as polyphenols, carotenoids and vitamins. Moreover, previous studies of our research group have demonstrated the beneficial effect of PS enriched milk-based fruit beverages on oxidative stress prevention and intestinal epithelia integrity maintenance in Caco-2 cells [32], as well as, their systemic anti-inflammatory properties, in hypercholesterolemic post-menopausal women, through the serum increase of anti-inflammatory cytokine IL-10 with concomitant reduction of IL-1β, cytokine which play an important role on the development of IBD [33].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, milk-based fruit beverages could be a suitable nutritional matrix for this purpose due to its low-fat content and good sources of bioactive compounds such as polyphenols, carotenoids and vitamins. Moreover, previous studies of our research group have demonstrated the beneficial effect of PS enriched milk-based fruit beverages on oxidative stress prevention and intestinal epithelia integrity maintenance in Caco-2 cells [32], as well as, their systemic anti-inflammatory properties, in hypercholesterolemic post-menopausal women, through the serum increase of anti-inflammatory cytokine IL-10 with concomitant reduction of IL-1β, cytokine which play an important role on the development of IBD [33].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that phytosterols, specifically β-sitosterol, modulate Th1/ Th2 balance by inducing Th1 secretions in pregnant women. -Sala et al, 2018;Bouic et al, 1996Bouic et al, , 1999Desai et al, 2009;Yeganeh et al, 2005). However, maternal Th1/ Th2 balance has rarely been correlated with phytosterols.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study has reported sitosterol/sitosterol-glucoside mixtures decrease stress-induced IL-6 production in marathon runners (Bouic et al, 1999). A mixture of campesterol and β-sitosterol has been suggested to increase IL-10 concentration, with a concomitant significant reduction of IL-1β in postmenopausal women (Alvarez-Sala et al, 2018). However, no association was detected between sitosterol (or campesterol) and serum TNF-α (or IL-6) concentrations in subjects with impaired glucose tolerance (Hallikainen et al, 2007).…”
mentioning
confidence: 93%
“…The hypocholesterolemic effect of milk-based fruit beverages enriched with plant sterols (PS) has previously been demonstrated, obtaining a beneficial effect on the serum inflammatory status as well [1]. Galactooligosaccharides (GOS) are added to food products due to their health benefit by selectively stimulating the growth of specific members of the intestinal microbiota [2].…”
mentioning
confidence: 99%
“…Volunteers consumed daily 250 mL of a PS-enriched beverage (0.8%, w/v) with or without GOS (1.7%, w/v) for 6 weeks and serum samples were collected before and at the end of each intervention period. Total cholesterol serum levels were measured by a routine quality-controlled method [4] whereas cholesterol precursors (desmosterol and lathosterol) and metabolites (cholestanol), and PS contents (campesterol, stigmasterol and β-sitosterol) were measured by GC-FID [1]. Intake of both beverages (without and with GOS addition) led to a statistically significant decrease (p < 0.05) in total cholesterol serum levels (4.7-5.1%), without significant differences between beverages.…”
mentioning
confidence: 99%